The signatures of liver metabolomics and gut microbiota in high-fat diet fed mice supplemented with rhododendrol. Issue 24 (5th December 2022) - Li, Xiaoping; Wang, Yu; Yu, Chengwei; Yao, Yexuan; Chen, Xi; Deng, Ze-Yuan; Yao, Zhao; Luo, Ting
Abstract : The major metabolites of raspberry ketones, rhododendrol (RHO) have the potential for nonalcoholic fatty liver disease (NAFLD) amelioration. Abstract : As aromatic compounds found within red fruits and berries, raspberry ketones (RK) have the potential for nonalcoholic fatty liver disease (NAFLD) amelioration. However, the mechanism of RK on NAFLD is unclear, and their bioactive metabolite is unknown. As the major metabolites of RK that are mainly distributed in the liver, rhododendrol (RHO) is used in our current study to test whether RHO accounts for the beneficial effect of RK on NAFLD and the underlying mechanism. In a 16-week trial, RHO significantly decreased final body weight, improved serum lipid profile and ameliorated liver inflammation. Moreover, RHO changed the gut microbiota composition, including lean phenotype-related genera, such as Bacteroides, Bilophila, Oscillibacter, Lachnospiraceae_bacterium_28_4 and Bacteroides sartorii . Liver metabolomics analysis indicated that RHO enhanced the abundance of metabolites related to alanine, aspartate, and glutamate metabolism, as well as arginine and proline metabolism. Spearman correlation analysis revealed that these metabolites were positively correlated with the gut genera enriched by RHO. Here, our findings suggested that the metabolic effects of RK might be partially attributed to its metabolite-RHO, and mice supplemented with RHO have dramatically altered hepatic metabolisms concurrent with shifts in specific gut bacteria.